Perceived Ease of Use as a Moderator in the Relationship Between the Online Tax System and Tax Service Quality - Dewi, Sari; Karjantoro, Handoko; Vera, Vera (Jurnal Akuntansi, 2024)
Abstract Purpose - The success of the online tax system is based on the existence quality of tax services and ease of use of the application. The low tax ratio proves that tax compliance in Indonesia is still relatively low. To overcome these problems, this study aims to examine the effect between the quality of tax services and the use of the online tax system and examine the effect of moderation of perceived ease of use of the online tax system and tax service quality. Design/methodology/approach - This study used cross-sectional data and a quantitative approach. Sampling is carried out by disseminating questionnaires to taxpayers in Indonesia.Findings - The results showed that there was a positive relationship between the tax service quality and the online tax system. In addition, it was found that there was a significant moderating influence between perceived ease of use and the relationship between online tax systems and tax service quality.Research limitations/implications - The Directorate General of Taxes can make this research an assessment of Taxpayers on the online tax system services provided, so that it is expected to continue to develop the tax system to make it easier for the public to use. The government can provide socialization of the use of the online tax system to the public so that people in Indonesia can understand and use this digital-based tax system. Keywords: Online Tax System, Tax Service Quality, and Perceived Ease of Use